ANN Assisted-IoT Enabled COVID-19 Patient Monitoring; IEEE Access; Vol. 9 - Ratkhor G. Gitandzhali; Garg S. Sakhil; Kaddum Zh. Zhorzh; Vu Yuley; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Alamri A. M. Atif M (2021, 2021)
Title screen